Do Digital Marketing Impact Business Performance? Emerging Views from Managers and Owners of Micro, Small and Medium Scales Enterprises in Nigeria - Silas Gontur; Adenike Odewumi Seyi; Yerima Sati Bakshak; Felix Dashe Awoena (Journal of Business & Management, 2023)
Micro, Small and Medium Enterprises (MSMEs) are engaged in recreation and economic wellbeing of a nation. They generate diversified sources of national income, improve a country’s competitive advantage and support economic development leading to suppleness of the economies. This study examines the influence of digital marketing on MSMEs performance in Plateau State, survey research design was used, data were obtained from 130 MSMEs in Plateau State through self – administered questionnaires and the study instruments were adapted from previous studies. The study instruments were subjected to determine the validity and reliability of the research instrument and subsequently to determine the hypothesized direct relationships among the variables through multiple regression analysis method. The findings revealed that social media marketing, e – mail marketing, internet marketing, and mobile marketing, are positive related to the performance scale of micro and medium scale enterprises in plateau state, while search engine marketing has no relationship with firm performance. The implication to the study is that digital marketing has a potential as marketing strategy to influence performance of small firms, the study will be of great importance to scholars because it a new subject to explore as a marketing strategy for MSMEs in competitive environment characterized rapid change in technology